Perfis bioquímicos séricos de equinos alimentados com diferentes dietas completas - Barbon, Isadora Macedo (2019)
The use of extruded and pelleted diets is becoming more and more frequent in equine nutrition, making it important to know the performance of animals confined receiving this type of diet. The objective was to compare the serum profile of horses kept in feedlot confined with a feeding management of pelletized and extruded complete diets. The experiment was carried out in the Vista Alegre horse farm in Uberaba-MG with four female horses distributed in a 4x4 Latin square scheme. The treatments were: D1 - 5 kg hay + 4 kg of extruded feed. D2 - 6 kg extruded feed + 500 g extruded mineral. D3 - 5 kg hay + 2 kg extruded feed + 2 kg pelleted feed. D4 - 5 kg hay + 4 kg pelleted feed. Four feeding cycles were performed, each with a period of ten days of adaptation to the test ration, followed by two days for the blood collection, so that each animal received in four periods. the four diets. The animals were housed in individual stalls, with feed trough and drinking water at will. Blood collection was performed once per period and sent to the laboratory for analysis of Cholesterol, Triglycerides, Urea, Creatinine, Total Proteins, CK, AST, Albumin, Phosphorus, Calcium, Magnesium, Iron. Regardless of the diets offered, we observed that these blood metabolites remained within the reference values for adult horses in maintenance, showing that they are not parameters for comparison of those complete diets studied.